Improving the humidity sensing below 30% RH of TiO2 with GO modification. (March 2018) - Sun, Linchao; Haidry, Azhar Ali; Fatima, Qawareer; Li, Zhong; Yao, Zhengjun
Graphical abstract: Highlights: Rutile phase TiO2 aggregates were prepared via thermal oxidation of pure Ti-discs, which is simple and inexpensive method. TiO2 aggregates with submicron particles based sensor exhibited ultra-high response ( R A / R H 2 O > 10 6 ) to 90% RH. Sensors based on TiO2 modified with GO exhibited improved sensitivity, stability and reproducibility. Abstract: The development of cost-effective, robust, and reliable humidity monitoring system is nowadays in high demand. To this context, humidity sensors based on rutile TiO2 aggregates were prepared via thermal oxidation of pure Ti-discs at 1000 °C. The sensors based on only TiO2 aggregates exhibited the ultra-high response of about six orders of magnitude (RA /R%RH ∼ 10 6 ) to 90% RH with a response time of 28 s and excellent stability. However, these sensors showed no response to RH below 30%, which limits their use in practical applications for such RH level monitoring. Although with a reduced response in high RH, the TiO2 modified with GO showed potential to overcome this drawback. To understand their functionality, the TiO2 aggregates and TiO2 /GO were further characterized by XRD, SEM, TEM, Raman and FT-IR spectroscopy. The presented results are of high interest in terms of wide range humidity monitoring, low-cost and simple synthesis route, and high stability.